Exploring Physical Activity and Barriers to Exercise in Transgender and Gender-Diverse Adults Initiating or Continuing Gender-Affirming Hormone Therapy - Emily Miro; Masaru Teramoto; Brett Toresdahl (Journal of Physical Activity and Health, 2026)
Background : Little is known about physical activity and barriers to exercise in transgender and gender diverse (TGD) adults. We examined the impact of gender-affirming hormone therapy (GAHT) on exercise comfort and perceived barriers to physical activity. Methods : An online survey was distributed to TGD adults initiating or continuing GAHT at a primary care clinic. Comfort with exercise and agreement with statements describing potential barriers to physical activity were assessed using Likert scales. Pre- and post-GAHT comfort levels were compared using Wilcoxon signed-rank tests, and association with psychosocial variables was examined using Spearman correlations. Results : Among 111 participants, comfort exercising at home increased significantly after GAHT (58%–88%, P < .001), while discomfort in sports leagues increased (68%–85%). Fear of harassment or bullying was significantly associated with greater declines in comfort in public gyms ( ρ = −.295, P = .006) and sports leagues ( ρ = −.397, P < .001). In gender-stratified analyses, all groups reported increased comfort at home, but transgender women uniquely experienced declines in public gym ( P = .002) and sports league comfort ( P < .001). Conclusions : TGD respondents reported increased comfort exercising at home and decreased comfort exercising in sports leagues post-GAHT. Barriers included fear of acceptance, harassment, and body discomfort. Post-GAHT changes in exercise comfort appear strongly influenced by psychosocial factors and setting-specific concerns, particularly for transgender women. These findings highlight the need for safer, affirming exercise environments and targeted strategies to reduce harassment and enhance access to physical activity for TGD adults.